Biodiesel Feedstock from Emulsions Produced by Aqueous Processing of Yellow Mustard. (1st April 2014) - Tabtabaei, Solmaz; Boocock, David G. B.; Diosady, Levente L.
Abstract: The multi‐stage treatment of stable oil‐in‐water emulsions produced during non‐enzymatic aqueous processing of dehulled yellow mustard flour with cyclic ethers [tetrahydrofuran (THF) and 1, 4‐dioxane] was investigated to produce a single‐phase oil‐solvent‐water miscella suitable for biodiesel production. While the single‐stage treatment of yellow mustard emulsion recovered 97 % and 95 % of the oil by using 4:1 THF:oil and 9:1 dioxane:oil weight ratios, respectively, miscella phases containing more than 7 % water formed, which made them unsuitable as biodiesel feedstock. Multi‐stage treatments of the emulsion using lower THF:oil and dioxane:oil weight ratios were further developed to produce oil‐solvent‐water miscella phases with low water content. While three‐stage extraction of emulsions using 0.5:1, 1:1, 1.5:1, and 2:1 dioxane:oil weight ratios did not destabilize the emulsion, three‐stage extraction using 0.5:1 and 0.75:1 THF:oil weight ratios effectively recovered over 97 % of the oil, resulting in the production of oil‐rich miscella phases containing only 1 % and 1.5 % water, respectively. These miscella phases were analyzed for free fatty acid and phosphorus contents and proved to be excellent feedstocks for the preparation of high‐purity methyl esters through single‐phase base‐catalyzed transmethylation.